"Victim Refuses to Cooperate": A Focal Concerns Analysis of Victim Cooperation in Sexual Assault Cases. Issue 2 (4th March 2017) - Kaiser, Kimberly A.; O'Neal, Eryn N.; Spohn, Cassia
Abstract: Research suggests that victim cooperation is a strong predictor of arrest and prosecution in sexual assault cases. Relatively little research has focused on identifying the factors that shape the decision to cooperate and the research that does exist is largely atheoretical. We address these gaps by examining victim cooperation using a revised version of the focal concerns perspective. We use data on cases reported to law enforcement agencies in Los Angeles to estimate models using factors situated within three victim focal concerns—crime seriousness, costs of cooperation, and likelihood of conviction—for three stages of the case process. We supplement these results with qualitative data from police reports regarding the reasons why victims refused to cooperate. The findings of this study provide initial support for the theoretical development of victim cooperation using the focal concerns perspective and provide potential guidance to criminal justice practitioners on how to increase victim cooperation.